Erroneous placement of central venous catheters in subclavian artery: Retrieval and successful hemostasis with a femoral closure device. Issue 5 (September 2022) - Verloh, Niklas; Scharf, Gregor; Bäumler, Wolf; Pfister, Karin; Oikonomou, Kyriakos; Stroszczynski, Christian; Uller, Wibke; Dollinger, Marco
Background: Retrospective evaluation of the safety and efficacy of the retrieval of misplaced central venous catheters (CVCs) in subclavian arteries using the femoral closure device Angio-Seal™. Methods: The clinical data of five patients (female, n  = 2; mean age, 55.0 years ± 11.9) in whom a misplaced CVC within a subclavian artery was removed followed by closure of the vessel entry site with 8-French (F) Angio-Seal™ was analyzed. Results: In 4/5 patients (80%; CVC diameter, 7-8F) the procedure was technically successful without complications. In 1/5 patients (20%; CVC diameter, 11.5F) the procedure failed and an additional covered stent was placed for successful closure of the vessel entry site. There were no complications associated with the Angio-Seal™ or stent implantation during follow-up. Conclusion: Retrieval of a misplaced CVC within a subclavian artery using the percutaneous closure device Angio-Seal™ is quite safe and effective; however, caution is required if there is a mismatch in the diameter of the Angio-Seal™ and CVC. In the case of procedure failure, successful closure of the vessel entry site can be achieved by covered stent placement.